2019
DOI: 10.1111/apa.14693
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of neurodevelopmental outcomes at 4–10 years in children born at 22–25 weeks gestation

Abstract: Aim To update our meta‐analysis on neurodevelopmental disability rates in children born at 22–25 weeks gestation. The main outcome measure was rates of neurodevelopmental disability in survivors at age 4–10 years. Methods We used a peer‐reviewed electronic and grey search to identify articles. Two authors independently reviewed cohorts published after May 2012 with: born ≥1995 in a developed nation; assessed at 4–10 years; prospective; >65% follow‐up; definitions for neurodevelopmental disability as per the EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Eligible cohort studies were identified from a recent meta-analysis; the methods are published elsewhere 9 10. In brief, a peer-reviewed search strategy of published and grey literature sources, developed with a librarian, was used to gather studies published between 2005 and 2016 (online supplementary appendix 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eligible cohort studies were identified from a recent meta-analysis; the methods are published elsewhere 9 10. In brief, a peer-reviewed search strategy of published and grey literature sources, developed with a librarian, was used to gather studies published between 2005 and 2016 (online supplementary appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, a peer-reviewed search strategy of published and grey literature sources, developed with a librarian, was used to gather studies published between 2005 and 2016 (online supplementary appendix 1). Prospective cohort studies examining neurodevelopmental outcomes of children aged 4–10 years born at 22–25 weeks gestation were eligible for inclusion 9 10. Of 15 eligible cohort studies identified, one study was excluded (no full-text publication), leaving 14 studies in our final sample (online supplementary appendix 2).…”
Section: Methodsmentioning
confidence: 99%
“…If Judy survives, she has approximately 80 more years left to live. If (and at the risk of discriminating on the basis of disability) we further consider the possibility that Judy might survive with severe neurodevelopmental impairment we would estimate that she has a 17% [95% CI: (13%, 22%)] chance of having a life-long severe disability (Ding et al 2019). For Jim, we have no data on his long-term outcomes but respiratory impairments seem to be described.…”
Section: Age Gestational Age or Measurable Outcomes?mentioning
confidence: 99%
“…The allocation decision would probably be similar if she was born at 22 weeks. If that were the case, she would have a 23% chance of survival (10-50% depending on where she was born) and 42% chance of long-term neuro-morbidity (Backes et al 2019;Ding et al 2019;Rysavy et al 2015). Her chance of survival is probably similar to Jim's (Arentz et al 2020;Weiss and Murdoch 2020;Zhou et al 2020), but Judy would still live longer.…”
Section: Age and Gestational Age Biasesmentioning
confidence: 99%
“…Readers may also be interested in Ding et al. 's meta‐analysis of neurodevelopmental outcomes of children born at 22–25 weeks of gestation and assessed at 4–10 years.
…”
Section: Active Care Of Periviable Infants Did Not Follow Consensus Ementioning
confidence: 99%